Housing and Health: Linking Population Health Survey Data to Housing Assistance Data - Golden, Cordell; Mirel, Lisa (International Journal of Population Data Science, 2018)
Introduction The linkage of survey data with administrative data enhances the scientific value and analytic potential of both sources of information. Combining multiple data sources facilitates richer analyses and allows data users to answer research questions that cannot be addressed easily using a single data source. Objectives and Approach Recently, the United States National Center for Health Statistics (NCHS) and Department of Housing and Urban Development (HUD) collaborated to link two population health surveys conducted by NCHS with housing assistance program data maintained by HUD. The resulting linked data files enable researchers to examine relationships between the receipt of federal housing assistance and health. In this talk, we will describe some of the challenges faced when initiating a data sharing agreement between two federal agencies governed by distinct legislative authorities, particularly issues related to legal requirements and data access. Results We will describe each of the data sources used in the linkage as well as the methodology used to combine the data. Lastly, the discussion will focus on the inter-agency collaboration that led to the production of the supporting technical documentation developed to assist researchers using the linked data files. The linkage of NCHS survey data and HUD administrative data serves as an example of how two agencies were able to overcome challenges to successfully form a data sharing partnership as a cost-effective means to develop a robust data source that benefits the collaborating agencies as well as policy makers and outside researchers. Conclusion/Implications Both agencies anticipate that this partnership will continue as additional survey and administrative data are collected.